PENGARUH SERVICESCAPE DAN GAYA HIDUP TERHADAP NIAT BERKUNJUNG ULANG DIMEDIASI KEPUASAN (STUDI EMPIRIS CAFÉ DI JOMBANG) - Indra Kurniawan (JURNAL LENTERA BISNIS, 2024)
The current café business has grown so rapidly, the level of competition is also getting tougher, marked by the emergence of various kinds of café concepts that have their own charm, have their own characteristics raised, provide a customer experience. This study aims to examine whether servicescape and lifestyle affect the intention to revisit, and satisfaction is a mediating variable from the influence of the two independent variables. The research method used an explanatory approach, the data was obtained through distributing questionnaires to cafe customers in Jombang and its surroundings, there were 182 respondents. The results showed that servicescape had an effect on the intention to revisit, and lifestyle also had an effect on the intention to revisit, meanwhile satisfaction became a mediating variable (partial mediation) of the two independent variables on the intention to revisit. Keywords: Servicescape, Lifestyle, Satisfaction, Revisit Intention.